The Dynamics of Single Parent Family Resilience: An Islamic Family Law Approach and Sociological Analysis - Putri, Shindy Qorti; Putri, Siska Elasta; Nofrianti, Mami (Institut Agama Islam Negeri Batusangkar, 2024)
The primary issue addressed in this study is the impact of the lean season, which significantly reduces rice field yields. The study aims to explore the strategies employed by single-parent families in Nagari Pagaruyung who work as farmers to maintain family resilience, along with the supporting and hindering factors in this effort. The research utilizes a qualitative approach with a phenomenological method. Data collection is conducted through interviews and documentation, supported by source triangulation, which involves asking the same questions to multiple informants. The findings reveal that single parents in Nagari Pagaruyung adopt various strategies to sustain family resilience, including diversifying their jobs, with farming being one of them. During the lean season, they undertake additional measures such as seeking alternative income sources, utilizing savings, and borrowing money from relatives. The driving factors for these families include affection for their children and intrinsic motivation within the family. On the other hand, the inhibiting factors include economic challenges and the difficulty of balancing time between work and children